ChemInform Abstract: Rh(III)‐Catalyzed Synthesis of 1‐Substituted Isoquinolinium Salts via a C—H Bond Activation Reaction of Ketimines with Alkynes. Issue 33 (19th August 2014) - Senthilkumar, Natarajan; Gandeepan, Parthasarathy; Jayakumar, Jayachandran; Cheng, Chien‐Hong
Abstract Ruthenium complexes can also be employed as catalysts.